Clinicopathological Characteristic of Radioactive Iodine-Refractory Differentiated Thyroid Carcinoma at Dr. Hasan Sadikin Hospital 2016-2021 - Ayni, Tutik Nur; Agustina, Hasrayati; Hernowo, Bethy Suryawathy; Koesoemah, Raden Erwin Affandi Soeriadi; Azhar, Yohana (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2024)
Background Initial therapy for differentiated thyroid carcinoma (DTC) is thyroidectomy with or without cervical lymph node dissection. Furthermore, radioactive iodine (RAI) is given to patients by considering risk stratification and other patient factors. Although most cases of DTC have a good prognosis after standard therapeutic approaches, the risks of local recurrence and distant metastases can be as high as 20% and 10%. Among these patients, two-thirds showed RAI-refractory. This is concerning because 10-year survival rate is less than 10%. This study aimed to analyze the clinicopathological characteristics of RAI-refractory DTC. Methods This is a case-control study. Data was collected from the Department of Nuclear Medicine and Molecular Theranostics and Department of Anatomical Pathology, Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin Hospital, Bandung period 1 January 2016-31 December 2021. Results Clinicopathological factors associated with RAI-refractory DTC are age, sex, aggressive histologic subtype, LVI (lymphovascular invasion), m-ETE (microscopic extrathyroid extension), TNM (tumor, nodal, metastasis) stage, and ENE (extranodal extension), with p-value <0.05. Meanwhile, there was no significant difference in the histologic type between RAI-refractory and non-RAI-refractory groups. Conclusion In the pathology report, it is necessary to include prognostically relevant tumor histopathological characteristics. In addition to histologic type, histologic subtype, and tumor size, other features such as presence and extent of capsular invasion, LVI, microscopic and macroscopic ETE, ENE, and number and size of metastatic lymph nodes, have been shown to provide additional prognostic information and are required in standard pathology reports for DTC.